Prevalence of psychological markers of overtraining amongst elite male field hockey and soccer players in top national leagues in Kenya - Richard, N. K.; Mwisukha, A.; Bulinda, M. (International Journal of Sports Science, 2020)
The purpose of this study was to assess the prevalence of psychological markers of overtraining amongst elite male field hockey and soccer players in top national leagues in Kenya. The study was limited to selected mood states of anger, confusion, depression, fatigue, tension and vigour that are applicable when assessing the mood states of athletes in exercise settings. The target population for the study comprised elite male hockey and soccer players in top national leagues in Kenya. A total of 232 participants (116 hockey players and 116 soccer players) were included in the study resulting into response rate of 71.6%. The research adopted the standard version of the Profile of Mood State questionnaire (POMS). T-test was used to determine whether there was any significant difference between the mood state profiles of hockey and soccer players at a significance level of P= 0.05. Results indicated that the two groups (elite male hockey and soccer players) differed significantly as far as mood state profiles were concerned. In conclusion, the study revealed that psychological markers of overtraining were prevalent among elite male hockey and soccer players. The study therefore recommended that there is need for coaches and other stakeholders to assess their players` mood states during the playing season.